2011
DOI: 10.1108/03068291211188910
|View full text |Cite
|
Sign up to set email alerts
|

The role of institutions in economic development

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…High institutional quality is crucial because it leads to better improvements to challenge the existing technology and products whilst at the same time allow them to gain profit from their inventions and help to promote technological change and innovations. This is vital for economic efficiency (Daron Acemoglu et al 2008;Rasha Hashim Osman, Constantinos Alexiou and Persefoni Tsaliki 2012).…”
Section: Vat Country Governance and Economic Efficiencymentioning
confidence: 99%
“…High institutional quality is crucial because it leads to better improvements to challenge the existing technology and products whilst at the same time allow them to gain profit from their inventions and help to promote technological change and innovations. This is vital for economic efficiency (Daron Acemoglu et al 2008;Rasha Hashim Osman, Constantinos Alexiou and Persefoni Tsaliki 2012).…”
Section: Vat Country Governance and Economic Efficiencymentioning
confidence: 99%
“…In the literature, institutions play a significant role in growth and development processes (Acemoglu & Robinson, 2013;North, 1990), in particular contributing to understanding those processes in developing countries (Acemoglu & Robinson, 2013;Easterly et al, 2004;Osman et al, 2011;Świerczyńska & Kryszak, 2019). However, there is no consensus on a particular set of institutions that significantly influence development processes in the S-SA countries.…”
Section: Introductionmentioning
confidence: 99%
“…Rodrik (2000) highlighted that democracy helps build better institutions. On account of the role of institutions in shaping economic performance, numerous studies have attributed differences in economic performance to differences in institutional quality (Acemoglu & Robinson, 2008; Besley & Ghatak, 2010; Christensen & Lægreid, 2005; Commander & Nikolski, 2010; North, 1990; North, 1991) Osman et al (2012) examined the relationship between institutional quality and economic performance in 27 sub-Saharan African countries and concluded that improving the institutional infrastructure plays a key role in delivering long-run economic development and social prosperity.…”
Section: Introductionmentioning
confidence: 99%
“…
This study attempts to assess the variations in households' confidence levels in various sociopolitical institutions with varying socioeconomic and cultural characteristics across major Indian states based on two rounds of the India Human Development Survey (IHDS-I, 2004(IHDS-I, -2005 IHDS-II, 2011-2012. It traces the presence of a lower confidence level of households in governance institutions compared with other institutions, implying a deficit of households' confidence in this component against the overall confidence score, which marginally improves over time.
…”
mentioning
confidence: 99%